Building connectivity at the research-policy interface in Aotearoa through a public sector postdoctoral fellowship scheme - Truax, Olivia (New Zealand Science Review, 2022)
Improving connectivity at the research-policy interface and supporting career development for early career researchers are twin goals of government-funded research systems in Aotearoa New Zealand and globally. The Aotearoa Ministry for Business, Innovation, and Employment (MBIE) began the process of overhauling the research system to achieve these, and other, goals through Te Ara Paerangi Future Pathways programme in 2021. Here, I propose a public sector postdoctoral fellowship scheme to place PhD graduates into roles within central government agencies, which MBIE could implement during the first phase of Te Ara Paerangi Future Pathways reforms. The Fellowship would strengthen collaboration at the research-policy interface and provide a low investment, high impact, opportunity to retain talent in Aotearoa by developing flexible career pathways for PhD graduates.